Influencia del método TEACCH en la enseñanza a estudiantes con trastorno del espectro autista TEA en la unidad educativa Anne Sullivan - Almachi Aucaquizhpi, Mariana (2017)
The present research is based on the influence of the TEACCH method in teaching students with autism spectrum disorder (autism spectrum disorder) within the Anne Sullivan Educational Unit, which tries to solve the following question: How to promote an adequate application of pedagogical methods in teaching learning in students with ASD of the initial level II and medium sub-level (5th and 7th EGB)? The context of this research is developed in the Anne Sullivan Educational Unit itself which is located in the Chongón Parish, located in the Km 14 ½ way to the Coast in the city of Guayaquil, Guayas Province, this school institution that is divided in inclusive education and specialized education. In relation to the methodological design, the present research was a bibliographical - documentary, and field, with mixed approach, with exploratory and descriptive scope, used observation techniques, and surveys directed to teachers and parents, a discretionary sampling was done six students who are included in the initial level II and average sub-level comprising 5to and 7th of GBS belonging to the morning session. Therefore, within the present…....